DISCRETE SEMIFLOW ON UNIFORM STRUCTURE OF SET F(S × T, X) - Dervishi, Neki (Matematichki Bilten, 2010)
In this paper is proved that, if \(T\) is a discrete topological abelian semigroup with the identity, and if \(X\) is a Hausdorff uniform space, then the mapping \(δ(f,t)=f_t\), defines a general discrete semiflow on uniform structure of set \(F(S × T, X)\) relative to the relative uniformity of pointwise convergence.